Climate Smart Agriculture – A Path Towards Sustainable Crop Production - Kaur, Ramanjit; Singh, Teekam; Kumar, Sunil; Singh, Raj (Chronicle of Bioresource Management, 2023)
Climate smart agriculture (CSA) is an integrated approach to manage different landscapes like croplands, livestock, forests and fisheries to address the interlinked challenges of food security and climate change. Agriculture is facing so many challenges to fulfil the demands of our ever-growing population. A growing global population and changing diets are driving up the demand for food. Production is struggling to keep up as crop yields level off in many parts of the world, ocean health declines and natural resources including soils, water and biodiversity are stretched dangerously thin. By 2050, the world will need to produce about 70% more food to meet the requirements of an estimated 9 billion people and this will be the most difficult challenge to face the food security. The challenge is further intensified by agriculture’s extreme susceptibility to climate change. Climate change’s negative impacts are already there and being felt, in the form of rising temperatures, weather unpredictability, shifting agro-ecosystem boundaries, invasive crops and pests and more frequent extreme weather events. On farms, climate change is reducing crop productivity/yields, the nutritional quality of major cereal crops and decreasing livestock productivity. Substantial investments in adaptation will be required to maintain and/or enhance current farm yields and to food quality.